Effects of probiotic supplementation on lipid profile of women with rheumatoid arthritis: A randomized placebo-controlled clinical trial - Elnaz Vaghef-Mehrabany; Leila Vaghef-Mehrabany; Mohammad Asghari-Jafarabadi; Aziz Homayouni-Rad; Karim Issazadeh; Beitullah Alipour (Tabriz University of Medical Sciences, 2017)
Background: Probiotics are live beneficial microorganisms which may exert hypolipidemic effects through many mechanisms. Lipid profile disturbances are frequently reported in rheumatoid arthritis (RA) patients. The objective of this study was to evaluate the effects of Lactobacillus casei on serum lipids of RA women. Methods: In the present parallel randomized double-blind placebo-controlled clinical trial, 60 RA patients were recruited and divided into 2 groups. They received either a daily capsule containing 108 CFU of L. casei 01, or identical capsules containing maltodextrin, for 8 weeks. Anthropometric parameters, dietary intake and physical activity were assessed at 2 ends of the study. Serum levels of total cholesterol (TC), high-density lipoprotein-cholesterol (HDL-C), low-density lipoprotein-cholesterol (LDL-C) and triglyceride (TG) were measured. Independent-samples t test and analysis of covariance (ANCOVA) test, and paired t test were used to test between- and within-group differences, respectively. Results: There were no significant between- or within-group differences for demographic and anthropometric parameters, physical activity and dietary intakes, throughout the study. No statistically significant within-group changes were observed for serum lipids in either group; between-group differences were also insignificant by the end of study period (TC: -0.18 [-0.65, 0.29], P = 0.801, HDL-C: -1.66 [-19.28, 15.59], P = 0.663, LDL-C: -2.73 [-19.17, 13.73], P = 0.666, TG: 0.12 [-19.76, 20.00], P = 0.900). Conclusion: Lactobacillus casei 01 could not improve serum lipids in RA patients. Further studies using probiotic foods and different probiotic strains are suggested.